Meaning and Replicability of Social Psychological Experiments: A Personal Account - Rijsman, John B. (Research Papers, 2024)
In this paper I describe the gradual evolution of experimental social psychology from a so called “science of discovery”, with invariant findings over time and space, to an art of theatrical reflection with self-made reproductions of social life to so engage in more thoughtful action. I do this by means of a narrative account of my sixty year long personal experience with the various changes in the discipline, from the many cases of non-replicability early in my career, to the splendid discovery by vigilant students at my department of the probably most impressive case of fraud in the history of the social sciences, to the persistent denial of a need for a new logic by orthodox positivists in the discipline, even after more than half of the carefully designed replications of important experiments in the discipline failed. I look at this evolution through the lens of gradual objectification in science as a whole, from the most distant objects, such as stars, to the closer and closer reality of our own existence, namely the production and processing of meaning, and the inevitable recursivity (historicity) and incompleteness (one cannot include one’s own discourse in the discourse one has at that moment) of that endeavour. I also describe moments of institutional evolution, its political besides scientific interest, and encounters with the most influential protagonists in the development of the new logic. I also reflect a moment on the theoretical and methodological implications of that new logic, and end with showing how the theme of social engagement and the move toward cultivated action, rather than by freezing history in the so called truth of invariance, was actually the core idea in the work of Kurt Lewin, and has been used inadvertently in the subsequent use of experiments in the discipline, even by those who pretended to be the astronomers of the mind. But with the clear note that reflection on social life in the form of self-made reproductions of that life, is probably the most human thing we can do, and enables us to create culture, rather than blind evolution in merely physical or biological terms. So, making experimental social psychology a valuable tool of humanization as well, but only when properly used.